(untitled) (Journal of the College of Basic Education, 2022)
Densities (ρ) and viscosities (η) of ethyleneglycole solutions in the range 0.1 to 0.35 mol dm-3 in 2% and 5% (w/w) Dimethylsulfoxide (DMSO)-water mixtures have been measured at different temperatures (298.15,303.15,308.15 and 313.15 K) .From these experimental data , the apparentmolar volume ϕν,limiting partial molar volume ϕºν, the slop Sν , Jones-Dole A and B-coefficients , Gibbs free energy of activation for viscous flow of solution ∆G*, enthalpy ∆H* and entropy ∆S*were calculated .The results shows a strong ion-solvent interactions and weak ion-ion interactions and also indicate that the ethylene glycole acts as structure breakers.